Prediksi Penjualan Obat Menggunakan Metode Forecasting Exponential Smooting Models (Kasus pada Apotek Simpang F) - Sari, Putri Permata; Hidayat, Asep Toyib; Wijaya, Harma Oktafia Lingga; Armanto, A (LPPM STIKOM Tunas Bangsa, 2023)
Prediction is an attempt to predict future conditions through testing conditions in the past. The problem with the Simpang F Pharmacy is that the Pharmacy has not been able to predict drug sales in the future because the demand for drugs is increasing. In this study, the use of the Single Exponential Smoothing (SES) method was implemented to predict drug sales at the Simpang F Pharmacy based on previous data. The drug samples used were 8 drugs, namely Paracetamol 500 mg, Ketoconazol 200 mg, Paraflu, Ambroxol 30 mg, Piroxicam 20 mg, Antacids, Tera-F and Samtacid as many as 264 data, from February 2020 to October 2022. Data testing used the Rstudio programming. In analyzing the researchers used the stages of inputting data, viewing data plots, making predictions, and measuring the Mean Percentage Error (MAPE) error value. The prediction results of drug sales at the Simpang F Pharmacy are Paracetamol 422.4929, Ketoconazole 180.0739, Paraflu 860.0145, Ambroxol 337.0633, Piroxicam 175.0015, Antacids 839.1842, Tera-F 910.6769, and Samtacid 167.1121. With MAPE values of 10.62926 ,17.39772 ,9.727205 9.095175, 14.94 4.617481, 4.052524, and 9.727205. And the accuracy of the prediction results was Paracetamol 89.4%, Ketoconazole 82.2%, Paraflu 95.4%, Ambroxol 90.9 %, antacids 95.4%, Tera-F 96%, and Samtacid 90.3%. Accuracy is stated as accurate for predictions using the Single Exponential Smoothing (SES) method.